"Abundance-Producing (Kawthari) Development" in the Framework of Divine Morality in Ayatollah Jawadi Amuli's View - Seyyed Reza Husseini (حکمت اسرا)
One dimension of development in its broad sense is "economic development" which has been the highest social objective and ideal of most countries around the world in modern age, especially after World War II. Economic development started in western countries and is based on certain ideological, anthropological and moral principles. Therefore, many Muslim thinkers faced with question whether economic development is essentially praiseworthy? If so, is it compatible with Islamic beliefs and ethics? The present paper seeks to study the issue in theosophy philosopher Ayatollah Jawadi Amuli's view. The research findings indicate that there are two kinds of economic development in his view. One is praiseworthy (abundance-producing development) and the other is reprehensible (worldly wealth-producing development). Abundance-producing development includes in itself the constant growth of production, technological progress, scientific prosperity and abundance of welfare facilities, while it is based on divine moralities and values, as well. Thus, it is not only permitted but also obligatory. He has specified some theoretical parameters of such development in different fields such as production, distribution and consumption and believes that a complete model of such development can be designed and implemented by more scientific endeavors in value and knowledge propositions of Islam.